ответ: 1) x = (a + b) / (a - b); a ≠ b; 2) x = 2 · (m - n); 3) x = a + 1;
4) x = (3 · (m - n)) / (m + n); m ≠ - n
Объяснение:
1) a²x - b²x = a² + 2ab + b²; x · (a - b) · (a + b) = (a + b)²; x = (a + b)² / (a - b) · (a + b)
x = (a + b) / (a - b); a ≠ b
2) 3mx + 3nx = 6m² - 6n²; 3 · x · (m + n) = 6 · (m + n) · (m - n);
x = (6 · (m + n) · (m - n)) / 3 · (m + n); x = 2 · (m - n)
3) ax + x = a² + 2a + 1; x · (a + 1) = (a + 1)²; x = (a + 1)² / (a + 1) = a + 1; x = a + 1
4) m²x + 2mnx + n²x = 3m² - 3n²; x · (m + n)² = 3 · (m + n) · (m - n);
x = (3 · (m + n) · (m - n)) / (m + n)²; x = (3 · (m - n)) / (m + n); m ≠ - n
x+y=6
y=6-x
x² -5=6-x
x² +x -5-6=0
x² +x-11=0
D=1+44=45
x₁=(-1-√45)/2=(-1-3√5)/2= -0.5-1.5√5
y₁=6 - (-0.5-1.5√5)=6+0.5+1.5√5=6.5+1.5√5
x₂=-0.5+1.5√5
y₂=6 - (-0.5+1.5√5)=6+0.5-1.5√5=6.5-1.5√5
ответ: (-0,5-1,5√5; 6,5+1,5√5);
(-0,5+1,5√5; 6,5-1,5√5).